Distinct fatigue cracking modes of grain boundaries with coplanar slip systems. (November 2016) - Li, L.L.; Zhang, Z.J.; Zhang, P.; Yang, J.B.; Zhang, Z.F.
Abstract: Three groups of Cu bicrystals with their component grains sharing one common 111 slip plane were cyclically deformed. By careful design on the loading direction, coplanar slip systems operated in the two component grains. Three kinds of grain boundaries (GBs): a low angle grain boundary (LAGB), a high angle grain boundary (HAGB) and an incoherent twin boundary (ITB), were all impinged by coplanar slip bands (SBs) on both sides. Nonetheless, the three kinds of GBs showed different fatigue cracking behaviors: the fatigue cracks nucleated along the HAGB earlier than along the SBs which produced cracks earlier than both the LAGB and the ITB. It is found that the slip vectors of the two component grains deviate from each other to different degrees for the three kinds of GBs. Lattice dislocations tend to pile up at the HAGB due to the large difference between the slip vectors, while lattice dislocations tend to pass through the LAGB and the ITB ascribed to the small differences between the slip vectors. High ability of dislocation transmission can generate good strain compatibility and low stress concentration near the GBs so as to increase the intergranular fatigue cracking resistance. In addition, lattice dislocation transmission and boundary dislocation motion can induce migration of LAGB and ITB which could improve the intergranular fatigue cracking resistance by consuming part of plastic work done by the cyclic loading. Thus, fatigue cracking resistance of GBs with impingement of coplanar SBs can be improved by increasing the penetrability and mobility of the GBs. Graphical abstract: